2012
DOI: 10.1038/nmeth.2104
|View full text |Cite
|
Sign up to set email alerts
|

The Metatron: an experimental system to study dispersal and metaecosystems for terrestrial organisms

Abstract: Dispersal of organisms generates gene flow between populations. Identifying factors that influence dispersal will help predict how species will cope with rapid environmental change. We developed an innovative infrastructure, the Metatron, composed of 48 interconnected patches, designed for the study of terrestrial organism movement as a model for dispersal. Corridors between patches can be flexibly open or closed. Temperature, humidity and illuminance can be independently controlled within each patch. The modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(107 citation statements)
references
References 27 publications
5
102
0
Order By: Relevance
“…Results also suggest the potential for the evolution of dispersal to influence metapopulation and metacommunity dynamics by altering the connectivity depending on regional landscape heterogeneity. We acknowledge that empirical dispersal data are difficult to obtain [29]; however, we hope that experimental facilities designed to study dispersal such as the Metatron [66] and recent developments in spatial networks, least-cost-path analysis and other indirect methods to quantify dispersal and connectivity might address this issue (reviewed in [27,54]) and allow tests of the theoretical predictions demonstrated here.…”
Section: Resultsmentioning
confidence: 97%
“…Results also suggest the potential for the evolution of dispersal to influence metapopulation and metacommunity dynamics by altering the connectivity depending on regional landscape heterogeneity. We acknowledge that empirical dispersal data are difficult to obtain [29]; however, we hope that experimental facilities designed to study dispersal such as the Metatron [66] and recent developments in spatial networks, least-cost-path analysis and other indirect methods to quantify dispersal and connectivity might address this issue (reviewed in [27,54]) and allow tests of the theoretical predictions demonstrated here.…”
Section: Resultsmentioning
confidence: 97%
“…The time an individual spent flying during the test was calculated, with high values reflecting good mobility. This test has been described previously (Ducatez et al, 2012b) and is known as a good proxy of dispersal in experimental metapopulations (Legrand et al, 2012). Butterflies were never harmed by the test and previous studies showed that other tested butterflies flew and mated in experimental conditions (Ducatez et al, 2012b;Trochet et al, 2013).…”
Section: The Journal Of Experimental Biology 216 (16) Flight Capacitymentioning
confidence: 90%
“…This implies that dispersers on the one hand and residents on the other hand may harbour the same characteristics. For example, in P. brassicae, dispersers have been shown to exhibit longer wings and higher mobility than residents (Legrand et al, 2012). Dispersers and residents may also use different types of movements.…”
Section: The Journal Of Experimental Biology 216 (16)mentioning
confidence: 99%
“…measures of bird dispersal at the Savannah River Site, [158]). Another example is the Metatron, a structure of 48 patches of 100 m 2 arranged on a grid and connected by corridors, which allows to study dispersal behaviours of small animals over months to years [159]. Field data provide weaker tests of theories than do experimental tests, since causes and consequences may not really be disentangled in the absence of manipulation, and since diverse factors may interact to select for or against dispersal.…”
Section: Empirical Considerationsmentioning
confidence: 99%